ANALISIS KECERDASAN EMOSI DAN MANAJEMEN KONFLIK - Aisyah .AR, Siti; Umari, Tri; Arlizon, Raja (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This study aims to determine the level of emotional intelligence of students, To know the picture perindenter kecerdaan emotions of students, To know the level of conflict management students who have on him, To know the picture of student conflict management indicators. The sample in this research is all students of SMP class VIII which amounted to 134 people. The result of this research is the emotional intelligence of students in general is in the high category with the percentage of 76.9%, then in the middle category with the percentage of 14.2%, and then in very high category with the percentage of 8.9%, students' emotional intelligence per-indicator of the most Students are selected on the indicators of managing self-emotion, and the least are indicators of recognizing self-emotion. The average student conflict management strategy lies in a compromise strategy.Keywords: Analysis, Emotional Intelligence, Conflict Management